Decay of the transient Cu B-CO complex is accompanied by formation of the heme Fe-CO complex of cytochrome cbb 3-CO at ambient temperature: evidence from time-resolved fourier transform infrared spectroscopy - Stavrakis, Stavros; Varotsis, Constantinos; Koutsoupakis, Constantinos (My University, 2002)
Time-resolved step-scan Fourier infrared spectroscopy has been used to study the CO-bound cbb 3-type cytochrome c oxidase from Pseudomonas stutzeri at room temperature. We observe a single band in the FTIR spectrum at 1956 cm -1 (β-form). The time-resolved data indicate that upon photolysis, CO is transferred from heme b 3 (v CO = 1956 cm -1) to CuB (v CO = 2064 cm -1). The decay of the 2065 cm -1 peak (t 1/2 = 120 ± 16 ms) and the development of the 1956 cm -1 peak (t 1/2 = 144 ± 8 ms ) suggest that formation of the Fe-CO complex is concurrent with the decay of the CuB-CO complex. The intensity ratio of the Fe-CO/CuB-CO (2.15) remains constant for all data points, and thus we conclude that no fraction of CO escapes the binuclear center at 293 K
Keywords: Carbon monoxide; Copper compounds; Fourier transform infrared spectroscopy; Cytochrome; Heme; Iron